Upaya Meningkatkan Keterampilan Membaca melalui Media Kartu Huruf Siswa Kelas I SD Negeri 30 Cakranegara - Istiningsih, Istiningsih (Lembaga Yasin AlSys, 2022)
This study aims: 1) To find out the use of letter card media in learning Indonesian can improve the reading skills of grade I students at SD Negeri 30 Cakranegara; 2) To find out the improvement of speaking skills in learning Indonesian through the media of letter cards for first grade students of SD Negeri 30 Cakranegara. This research was designed using Classroom Action Research. The subjects in this study were the first grade students of SD Negeri 30 Cakranegara, totaling 29 people, consisting of 17 female students and 15 male students. While the research procedure goes through the stages of planning, implementing actions, observing, and reflecting. The results showed that the application or use of letter card media in Indonesian language learning can improve student learning outcomes, when teaching and learning activities take place, namely from the number of students, namely 29 people, whose scores are equal to or more than the KKM totaling 27 people, and if the percentage is 93, 10%. This shows that there is an increase from the initial conditions and the first cycle, namely from the number of students who completed as many as 19 people 65.56% then to 24 people 82.76% and increased again to 27 people 93.10%. Based on the results of this study, it can be concluded that learning Indonesian by applying or using letter card media can improve the reading skills of first grade students at SD Negeri 30 Cakranegara.